2020
DOI: 10.4014/jmb.2002.02033
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter pullorum sp. nov., Isolated from Chicken Meat

Abstract: The earliest account of Acinetobacter species dates back to 1911 when Beijerinck described an organism isolated from soil, originally named Micrococcus calcoaceticus [1]. The current genus designation was initially proposed by Brisou and Prévot in 1954, based on motility [2]. In 1968, a comprehensive survey completed by Baumann et al. provided sufficient data for a group species previously classified to at least 15 different genera and species and reclassified them to a single genus, for which the name Acineto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…A comparison of the physiological and biochemical features of the two type strains shows phenotype coherence, which is summarized in Table S2 in the supplemental material. According to previous reports ( 14 ), A. pullorum and A. portensis are different in the acidification of d -glucose and utilization of β-alanine and d -glucose, which is likely due to intraspecies variability or assay conditions. Based on principles by the International Code of Nomenclature of Bacteria ( 12 ), A. pullorum has the priority of species name over A. portensis .…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…A comparison of the physiological and biochemical features of the two type strains shows phenotype coherence, which is summarized in Table S2 in the supplemental material. According to previous reports ( 14 ), A. pullorum and A. portensis are different in the acidification of d -glucose and utilization of β-alanine and d -glucose, which is likely due to intraspecies variability or assay conditions. Based on principles by the International Code of Nomenclature of Bacteria ( 12 ), A. pullorum has the priority of species name over A. portensis .…”
Section: Resultsmentioning
confidence: 90%
“…During the process of studying WCHAc060012 T and WCHAc060115 T , we also found a pair of synonyms, namely, A. pullorum and A. portensis . A. pullorum B301 T was isolated from raw chicken meat at a local market in Korea ( 14 ). It has been shown that A. pullorum B301 T is closely related to Acinetobacter celticus ANC 4603 T ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a phylogenetic tree was reconstructed using 361 core genes present in all of the reference genomes used in this study (Table S1) according to the methods described previously [34]. Briefly, protein-coding genes present in the genomes were identified using Prodigal software [35] and protein sequences in all genomes were clustered with 50 % sequence identity and 80 % alignment cutoffs using Linclust software [36].…”
Section: Genome Featuresmentioning
confidence: 99%